Gas-sensing properties of zinc ferrite nanoparticles synthesized by the molten-salt route - Darshane, Sonali L.; Deshmukh, Rupali G.; Suryavanshi, Shankar S.; Mulla, Imtiaz S. (Journal of the American Ceramic Society, 2008)
Zinc ferrite (ZnFe2O4) nanoparticles have been synthesized at 700 degrees C using sodium chloride as a growth inhibitor. Single-phase formation of spinel zinc ferrite having crystallite size in the range of 15-20 nm was observed by XRD and confirmed by TEM. In the present work, the gas-sensing properties of these zinc ferrite nanoparticles toward ethanol, LPG, H-2, NOx. SOx, and H2S have been studied. It was found that they exhibit excellent selective sensitivity toward 200 ppm of H2S at the operating temperature of 250 degrees C, and thus this nanosized ferrite is expected to be useful in an industrial application as a potential H2S gas sensor.

Gas sensing properties of magnesium ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Patil, R. P.; Sasikala, R.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2009)
Polycrystalline magnesium ferrite (MgFe(2)O(4)) was prepared by the co-precipitation method. The synthesized compound was characterized for their phase and morphology by X-ray diffraction and scanning electron microscopy, respectively. Conductance responses of the (MgFe(2)O(4)) were measured towards gases like hydrogen sulfide (H(2)S), liquefied petroleum gas (LPG), ethanol vapors (C(2)H(5)OH), SO(x), H(2), NO(x), NH(3), methanol, acetone and petrol. The gas sensing characterstics were obtained by measuring the sensitivity as a function of various controlling factors like operating temperatures and concentrations of gases. It was found that the sensor exhibited various responses towards these gases at different operating temperatures. Furthermore; the MgFe(2)O(4) based sensor exhibited a fast response and a good recovery towards petrol at temperature 250 degrees C. The results of the response towards petrol reveal that (MgFe(2)O(4)) synthesized by a simple co-precipitation method, would be a suitable material for the fabrication of the petrol sensor. (C) 2009 Published by Elsevier B.V.
Keywords: Ferrites; Gas sensor; X-ray diffraction and scanning electron microscopy